1967
DOI: 10.1128/jb.94.5.1764-1777.1967
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Metabolism of Marine Bacteria XVI. Formation of Protoplasts, Spheroplasts, and Related Forms from a Gram-negative Marine Bacterium

Abstract: When cells of a marine pseudomonad were washed and suspended in 0.5 M sucrose, they retained their rod shape, but thin sections, when examined in an electron microscope, revealed that the outer layer of the cell wall had separated a considerable distance from the cytoplasmic membrane. Treatment of such cells with lysozyme alone produced no obvious change, but treatment with ethylenediaminetetraacetic acid (EDTA) alone caused the outer wall to disappear. A combination of EDTA and lysozyme resulted in the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 8 publications
(10 reference statements)
0
43
0
Order By: Relevance
“…The appearance of hexosamine-containing material at this point indicated that the expected release of outer double-track layer and the underlying (periplasmic space) layer of the cell wall had occurred (9). The cell form which arises when the outer three layers of the wall have been removed is referred to as a mureinoplast (6). Traces of alkaline phosphatase activity remained associated with the mureinoplasts formed.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The appearance of hexosamine-containing material at this point indicated that the expected release of outer double-track layer and the underlying (periplasmic space) layer of the cell wall had occurred (9). The cell form which arises when the outer three layers of the wall have been removed is referred to as a mureinoplast (6). Traces of alkaline phosphatase activity remained associated with the mureinoplasts formed.…”
Section: Resultsmentioning
confidence: 89%
“…Neither the loosely bound outer layer nor the outer double-track layer (cell wall membrane) showed evidence of more than traces of alkaline phosphatase activity. The cell form left after release of the loosely bound outer layer, the outer double-track layer, and underlying (periplasmic space) layer is a mureinoplast, a cell form bounded only by its cytoplasmic membrane and a layer of peptidoglycan (6). A small amount of the total alkaline phosphatase activity in the cells remained attached to this cell form and was, in part, released on treatment of the mureinoplasts with lysozyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All experiments described herein used rumen fluid medium, unless otherwise stated. At given times of incubation, cultures were harvested by centrifugation in a Sorvall RC-2B refrigerated centrifuge for 10 min at 15,000 x g. The optical density of the culture was measured at 660 nm. The optical densities of cultures of B. ruminicola, B. succinogenes, and M. elsdenii were correlated with the dry weight of the cells by means of a calibration curve following drying to a constant weight at 90 C. From the curve it was determined that an optical density of Cell extracts and enzyme assays.…”
Section: Methodsmentioning
confidence: 99%